Clinical outcomes of pediatric Anti-NMDA receptor encephalitis. (November 2020) - Shim, YoungKyu; Kim, Soo Yeon; Kim, Hunmin; Hwang, Hee; Chae, Jong-Hee; Choi, Jieun; Kim, Ki Joong; Yum, Mi-Sun; Ko, Tae Sung; Kim, Young Ok; Byeon, Jung Hye; Lee, Jiwon; et al.
Abstract: Objective: To investigate the clinical features and long-term outcomes of pediatric Anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis. Methods: Thirty-two anti -NMDAR encephalitis patients with positive anti -NMDAR antibody test results were recruited. Clinical outcomes were evaluated using the Clinical Assessment Scale in Autoimmune Encephalitis (CASE) and the modified Rankin Scale (mRS). Results: The median age of onset was 9.0 years (range, 0.7–17.2 years). Twenty-four patients (75.0%) were female. All patients received first-line immunotherapy including intravenous immunoglobulin and/or steroid therapy. The second-line immunotherapy was administered to 22 patients (68.8%). Clinical outcomes were evaluated in 27 patients who were followed for longer than 6 months after onset, among whom the median follow-up duration was 31.2 months (range, 6.3–82.9 months). The proportion of patients with ≤2 points on the mRS at their 12-month follow-up was 79.2% (19/24). The CASE scores of these 19 patients ranged from 0 to 5, with language and memory deficits accounting for most of these disabilities. When the outcome was assessed according to onset age (<12 years or 12–18 years), the younger group tended to show a slower recovery over their clinical course. Conclusions: Despite overall favorable clinical outcomes, mild cognitive problems, including language and memory, may persist in pediatric anti -NMDAR encephalitis patients. A specific outcome measure, such as CASE, should be adopted to delineate clinical outcomes and aid the development of individualized treatment plans. Highlights: Despite favorable outcome, mild cognitive and language deficit can persist in pediatric anti -NMDAR encephalitis patients. Younger onset patients (<12 years) tended to recover more slowly than older onset patients (12–18 years). Clinical outcome measure should be specific to delineate the differential effect on outcome according to age of onset.